Experiments with LDA and Top2Vec for embedded topic discovery on social media data—A case study of cystic fibrosis - Karas, Bradley; Qu, Sue; Xu, Yanji; Zhu, Qian (Frontiers in Artificial Intelligence, 2022)
Social media has become an important resource for discussing, sharing, and seeking information pertinent to rare diseases by patients and their families, given the low prevalence to the extraordinarily sparse populations. In our previous study, we identified prevalent topics from Reddit via topic modeling for Cystic Fibrosis (CF). While we were able to derive/access CF patients’ concerns/needs/questions, we observed challenges and issues with the traditional techniques of Topic Modeling, e.g., Latent Dirichlet Allocation (LDA) for fulfilling the task of topic extraction. Thus, here we present our experiments to extend the previous study with an aim of improving the performance of topic modeling, by experimenting on LDA model optimization and examination of the Top2Vec model with different embedding models. With the demonstrated results with higher coherence and qualitatively higher human readability of derived topics, we implemented the Top2Vec model with doc2vec as the embedding model as our final model to extract topics from a subreddit of Cystic Fibrosis (“r/CysticFibrosis”) and proposed to expand its use with other types of social media data for other rare diseases for better assessing patients’ needs with social media data.